Glaciers of Georgia - Tielidze, Levan (Springer, 2017)
This book gives the most detailed and comprehensive insights into the morphology, morphometry and dynamics of glaciers in the Georgian Caucasus region up to date. It examines the variability of valley glaciers after the Little Ice Age maximum and identifies glacial dynamics during historical periods. The reconstruction of glaciation in the Late Pleistocene and Holocene was conducted based on long lasting detailed glacial-geomorphological observations by the author. It further analyses moraine structures, river terraces, geodynamics of the relief, and snow and firn line locations derived from field surveys in most glacier basins in the southern and northern slopes of the Georgian Caucasus. A whole set of methodological approaches was applied including remote sensing and GIS, glacio-geomorphological, cartographical, aerial image processing and petrographic methods, unveiling accurate information about glaciers difficult to access, e.g., in the Abkhazeti and Tskhinvali regions.
Keywords: Glaciers -- Georgia (Republic); Glaciology -- Georgia (Republic); Georgia (Republic); elektronické knihy; electronic books